Use Of Phraseological Combinations In Uzbeki And English Languages - Gulmanovna, Yangibayeva Nazira (PT. Antis International Publisher, 2024)
The article discusses phraseological expressions in English and their equivalents in Uzbek. It is about the research works of scientists who studied the field of phraseology. Difficulties faced by translators are described.